OPTIMASI MAGNETIT TERSALUT ASAM HUMAT (Fe3O4-AH) SEBAGAI ADSORBEN METHYLENE BLUE - Rusda Vera Anggraini; Soerja Koesnarpadi; Nanang Tri Widodo (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Optimization of pH and contact time on the adsorption of methylene blue by magnetite coated with humic acid (Fe3O4-HA) using the batch method was studied. The synthesis of magnetite coated humic acid (Fe3O4-HA) was carried out by coprecipitation method with a ratio of 1:2 (w/w). Optimization of pH and contact time of magnetite coated humic acid (Fe3O4-HA) was carried out with 30 ppm methylene blue concentration and 0.1 g Fe3O4-HA mass. The optimum pH and optimum contact time of magnetite coated humic acid (Fe3O4-HA) were at pH 7 with adsorption percent of 99,93% and 120 minutes with adsorption percent of 93,88%. Keywords: Adsorption, Fe3O4-HA, Methylene Blue, Optimization